Social classes in Europe - Costa, A. F. (2015)
The current globalization context brings new questions to class analysis. After a brief review of the theoretical stance and the operationalization possibilities offered by today's sociology of social classes and stratification, this article presents a comparative analysis in which a selected set of social recomposition indicators is applied to the European Union as a whole and to each one of its countries. One of the main themes discussed throughout the article is the relative importance of national and global parameters in the structuration of class relations.